Enhanced Scalability In Social Network Application Using Presence Service - Prof. V. M. Deshmukh, Poonam G. Pachkawade , (International Journal of Scientific Research and Management (IJSRM), 2015)
Social network applications have become more and more in style on mobile devices. A mobile presence service is an important element of a social network application as a result of it maintains every mobile user’s presence data, like the present standing (online/offline), GPS location and network address, and additionally updates the user’s on-line friends with the data regularly. If presence updates occur often, the large range of messages distributed by presence servers could cause a measurability downside in an exceedingly largescale mobile presence service. to handle the matter, we have a tendency to propose associate degree economical and ascendable server design, referred to as Presence Cloud, that allows mobile presence services to support large-scale social network applications. once a mobile user joins a network, Presence Cloud searches for the presence of his/her friends and notifies them of his/her arrival. Presence Cloud organizes presence servers into a quorum-based server-to-server design for economical presence looking. It additionally leverages a directed search algorithmic program and a one-hop caching strategy to attain little constant search latency. we have a tendency to analyze the performance of Presence Cloud in terms of the search value and search satisfaction level. The search value is outlined because the total range of messages generated by the presence server once a user arrives; and search satisfaction level is outlined because the time it takes to go looking for the coming user’s friend list. The results of simulations demonstrate that Presence Cloud achieves performance gains within the search value while not compromising search satisfaction.